Prinsip Pariwisata Berbasis Masyarakat dalam Pengembangan Desa Wisata Liang Ndara Kabupaten Manggarai Barat - Indra Ratna Sari; Nur Widiyanto; Damiasih Damiasih (Jurnal Syntax Admiration, 2024)
The purpose of the study is to understand and find out how the application of community-based tourism principles in the development of tourism Liang Ndara Tourism Village, West Manggarai Regency. The type of research used is descriptive qualitative research. Descriptive qualitative research is a type of research that aims to describe or describe completely about a phenomenon or situation being studied with actual facts. This research uses qualitative methods that are descriptive. The results of the study showed that Liang Ndara Tourism Village in West Manggarai Regency offers natural, cultural, and handicraft potential. Initially, its development was faced with challenges of limited human resources, funding, and waste management. Local communities are increasingly involved in tourism development, although it is difficult to change the initial mindset from the agricultural sector to tourism. The village applies 5 principles of community-based tourism, of which 3 have been well implemented. Positive impacts include new jobs, cultural assimilation, suave lifestyles, increased social interaction, community participation, and solidarity. However, the environmental impact still needs further attention, while the political impact is already visible. Efforts are ongoing to reduce negative impacts and increase benefits to local communities.